Comparison of proportional assist ventilation and pressure support ventilation in chronic respiratory failure due to neuromuscular and chest wall deformity. Issue 11 (1st November 2002) - Hart, N; Hunt, A; Polkey, M I; Fauroux, B; Lofaso, F; Simonds, A K
Abstract : Background: The physiological and symptomatic effects of proportional assist ventilation (PAV) and pressure support ventilation (PSV) were compared in stable awake patients with neuromuscular and chest wall deformity (NMCWD). Methods: Oxygen saturation (Sao 2 ), transcutaneous carbon dioxide (Tcco 2 ), minute ventilation (Ve ), tidal volume (Vt ), respiratory rate (RR), and diaphragm electromyography (EMGdi) were measured in 15 patients during both modes. Subjective effort of breathing and synchrony with the ventilator were assessed using visual analogue scales. Results: Three of 15 patients failed to trigger the ventilator in either mode and were excluded. In the 12 remaining patients there were similar improvements in Sao 2, Tcco 2, Ve, Vt, and RR during both modes. The mean (SD) percentage fall in EMGdi was greater during PSV (–80.5 (10.7)%) than during PAV (–41.3 (35.2)%; p= 0.01). Effort of breathing (p=0.004) and synchrony with the ventilator (p=0.004) were enhanced more with PSV than with PAV. Conclusion: Both PSV and PAV produced similar improvements in physiological parameters. However, greater diaphragm unloading was observed with PSV than with PAV, associated with greater symptomatic benefit. These findings suggest that tolerance to PAV may be compromised in patients with NMCWD.